2010
DOI: 10.2353/ajpath.2010.090428
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Deposits of IgA-Binding Streptococcal M Proteins in IgA Nephropathy and Henoch-Schönlein Purpura

Abstract: IgA nephropathy (IgAN) and Henoch-Schönlein purpura (HSP) are diseases characterized by IgA deposits in the kidney and/or skin. Both may arise after upper respiratory tract infections, but the pathogenic mechanisms governing these diseases remain unclear. Patients with IgAN (n = 16) and HSP (n = 17) were included in this study aimed at examining whether IgA-binding M proteins of group A streptococci could be involved. As M proteins vary in sequence, the study focused on the IgA-binding-region (IgA-BR) of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 60 publications
0
34
0
Order By: Relevance
“…and IgAN was hypothesized. Besides, streptococcal proteins were recognized by sera of IgAN patients [48,49]. In the present study, Streptococcus was also upregulated in Disease, implying that Streptococcus spp.…”
Section: Discussionmentioning
confidence: 59%
“…and IgAN was hypothesized. Besides, streptococcal proteins were recognized by sera of IgAN patients [48,49]. In the present study, Streptococcus was also upregulated in Disease, implying that Streptococcus spp.…”
Section: Discussionmentioning
confidence: 59%
“…Synthetic peptides corresponding to various regions of the M protein were also used. These peptides have been fully characterized and included the N-terminal hypervariable region of the M4 protein (M4N), the IgA-binding region of M4 (Sap4) and part of the C-repeat domain in the conserved region of the M22 protein (16, 34-36). The latter peptide has a 92.3% amino acid homology with the C-repeat domain of the conserved region of M4 (Figure 1B).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that children with IgAN are more likely than controls to have been infected with GAS expressing an IgA-binding M protein (22). Furthermore, we detected M protein-derived IgA-binding regions co-localizing with IgA in kidney samples of children with IgAN (16). These findings suggest a possible role of GAS strains expressing IgA-binding M proteins in the etiology and pathogenesis of IgAN.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemistry was performed to detect C5b-9 in human renal tissues according to a described method (25) with some modifications. Briefly, after peroxidase blocking, antigen retrieval was achieved by incubating the tissues with 0.1% protease type X1V (Sigma) for 20 min at 37 °C followed by blocking with 5% BSA in tris-buffered saline (TBS, Medicago) for 2 hr at room temperature.…”
Section: Immunohistochemistry For Detection Of C5b-9mentioning
confidence: 99%